Stock exchanges and regional competitiveness: the case of small German exchanges - Ruth Maria Boerdlein (European Regional Science Association (ERSA), 2002)
The analysis of financial centers focuses mainly on the competition between and changing roles of the major places. In the European context thus usually London, Paris, Frankfurt/Main and other national financial centers have become objects of investigation. The findings show that the recent reorganisation of financial centers in Europe under the conditions of widespread use of ICT with the possibility of remote access to exchanges, the development of innovative products on financial markets, and the advent of a single currency affects structures, organisation and specialization of the main actors within financial centers, i.e. banks and exchanges. The planned but failed merger between London Stock Exchange and Deutsche Börse AG in Frankfurt/Main in 2000 has probably been one of the publicly most noticed aspects of this development. The proposed paper wants to put a focus on less prominent features of current restructuring, namely the roles and strategies of minor German exchanges. The main idea is, that - although financial services are characterized by a spread of "de-spatialized" forms of service production-, strategies of regional development based (at least partly) on endogenous resources can be supported by regional financial institutions. The argument will be presented in three steps: At first the importance of a regional exchange for regional development has to be discussed on a theoretical base. This part will draw upon notions and considerations of the "glocalization" literature which stresses the ambivalent relationship between processes of globalization and disembedding on the one hand and re-interpretation of different forms of proximity (including spatial proximity) on the other hand. A second - also rather theoretical - part will consider the possible comparative advantages of minor exchanges in the context of the prevailing concentration processes. This section will therefore focus on possible strategies, which combine the access to highly liquid and innovative exchanges and the special regional knowledge available at regional institutions. The chances and risks of different strategies (alliances with strong national and/or international partners vs. "niche production") have to be discussed. In the third section the empirical findings of the analysis of different minor German exchanges situated in metropolitan regions (Berlin, Hamburg, Munich) will be presented and assessed according to the arguments developed in the preceeding parts. The contextualization not only in respect to the specific regional economic situation but also in respect to the history of the German decentralized system of exchanges and the main trends of restructuring of the "European exchange landscape" will be essential to this last part.
Keywords: 330